Differences in the Responses of Photosystems I and II in Cymbidium sinense and C. tracyanum to Long-Term Chilling Stress - Li, Jia-Wei; Zhang, Shi-Bao (Frontiers in Plant Science, 2016)
The susceptibility of photosystem I (PSI) and photosystem II (PSII) to chilling stress depends on plant species, and cyclic electron flow (CEF) plays an important role in photoprotection for some species under short stress periods. However, little is known about the responses of PSI and PSII to long-term chilling stress. We studied two orchid species -- Cymbidium sinense and C. tracyanum -- that differ in their capacity to adapt to low temperature, and exposed plants for 19 d to stress conditions that included 4°C and a light intensity of 250 to 350 μmol photons m-2 s-1. Meanwhile, we investigated their dynamic variations in Chl fluorescence and P700 parameters. After exposure to 4°C and 250 μmol photons m-2 s-1 for 6 h, PSI activity was maintained stable in both species, but stronger PSII photoinhibition was observed in C. sinense. During the long-term treatment, the maximum quantum yield of PSII was significantly reduced, with that decrease being greater in C. sinense. After 19 d of chilling treatment, the maximum photo-oxidizable P700 declined only slightly in C .tracyanum but dropped significantly in C. sinense. Linear electron flow was largely depressed during the long-term chilling treatment, especially in C. sinense. Meanwhile, C. tracyanum showed higher CEF activity than C. sinense. These results indicate that PSII is more sensitive to chilling-light stress than PSI in both species. The rate of PSII photodamage at chilling-light stress is higher in C. sinense than C .tracyanum, and CEF contributes to photoprotection for PSI and PSII under long-term chilling stress in C. tracyanum.